INNOVATIVE DEVELOPMENT STRATEGIES OF ENTERPRISES (American Journal of Pedagogical and Educational Research, 2026)
This article provides a comprehensive study of issues related to developing innovative and sustainable development strategies for enterprises in a competitive environment. The study analyses the economic, social, and ecological components of sustainable development - namely Environmental, Social, and Governance (ESG) indicators - in their interrelation, and elucidates the mechanisms ensuring the long-term competitiveness of enterprises on the basis of modern management approaches. As a result, an integrated development model is proposed and its practical significance is substantiated.